2011
DOI: 10.1017/s0021859610001292
|View full text |Cite
|
Sign up to set email alerts
|

The effect of rumen-protected methionine and choline on plasma metabolites of Holstein dairy cows

Abstract: SUMMARYForty Holstein dairy cows in their first and second lactations were used from 4 weeks prepartum to 10 weeks postpartum to investigate the effects of feeding ruminally protected methionine and choline on plasma metabolites. Cows were randomly assigned to one of the following treatments in a 2×2 factorial design 4 weeks before their expected calving dates, using randomized blocks based on parity: no supplement (control), 18 g/d of rumen-protected methionine (RPM) product, 60 g/d of rumen-protected choline… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(25 citation statements)
references
References 33 publications
0
25
0
Order By: Relevance
“…7, 2018 (Table 7). Others have reported increased (Janovick Guretzky et al, 2006 in the prepartum period; Elek et al, 2013;Amrutkar et al, 2015), decreased (Mohsen et al, 2011), or no effect (Janovick Guretzky et al, 2006 in the postpartum period; Xu et al, 2006;Ardalan et al, 2011) of RPC ion supplementation on circulating concentrations of TAG in dairy cows. This lack of agreement among laboratories may reflect different sampling times in relation to feeding, fewer samples collected than collected in the current experiment, and different amounts of fat intake.…”
Section: Fat Loadingmentioning
confidence: 99%
See 1 more Smart Citation
“…7, 2018 (Table 7). Others have reported increased (Janovick Guretzky et al, 2006 in the prepartum period; Elek et al, 2013;Amrutkar et al, 2015), decreased (Mohsen et al, 2011), or no effect (Janovick Guretzky et al, 2006 in the postpartum period; Xu et al, 2006;Ardalan et al, 2011) of RPC ion supplementation on circulating concentrations of TAG in dairy cows. This lack of agreement among laboratories may reflect different sampling times in relation to feeding, fewer samples collected than collected in the current experiment, and different amounts of fat intake.…”
Section: Fat Loadingmentioning
confidence: 99%
“…Feeding RPC ions increased plasma concentrations of TAG in dairy cows fed diets containing less than 3.5% ether extract on a DM basis (Janovick Guretzky et al, 2006, prepartum;Amrutkar et al, 2015). However, when diets contained more fat from whole cottonseed, supplementation of RPC ions had no effect on plasma TAG (Janovick Guretzky et al, 2006 postpartum;Xu et al, 2006;Ardalan et al, 2011). Therefore, the effect of RPC on influencing plasma TAG may depend on the intake of fat or the cow's energy status.…”
Section: Fat Loadingmentioning
confidence: 99%
“…Methionine can provide methyl groups for the de novo synthesis of choline (via S-adenosylmethionine). Choline can be oxidized to betaine, with methyl transfer from homocysteine and then Met (Zeisel & Da Costa 2009;Ardalan et al, 2011). Maskaľová et al (2014) suggest the importance of evaluating RPM and choline in ruminants and experiments in various physiological statuses.…”
Section: Introductionmentioning
confidence: 99%
“…However, there are insufficient dose-response data to make a clear case for choline requirement in transition dairy cows. Notwithstanding, the ability to reduce liver TAG has been commonly reported when supplementing with 15 g of RPC/d (59,(61)(62)(63) . The effects of supplementary RPC on biochemical, reproductive and productive features of dairy cows are summarised in Tables 1, 2 and 3.…”
Section: Provision Of Choline In Transition Dairy Cowsmentioning
confidence: 99%
“…In another study, DMI was increased by 8•4 % in cows supplemented with 30 g of RPC/cow per d (7•5 g of choline chloride) in the first 12 weeks of lactation (90) . Ardalan et al (61) reported that feeding 60 g of RPC/cow per d (15 g choline chloride) from the time of calving until week 10 of lactation increased DMI (22•1 v. 18•9 kg/d), whereas feeding the same amount of choline before parturition was not associated with increased intake. An interaction between body condition score (BCS) and DMI was reported by Zahra et al (60) .…”
Section: Choline and Dm Intakementioning
confidence: 99%